Penilaian Implementasi Green Supply Chain Management di UKM Batik Pekalongan dengan Pendekatan GreenSCOR - Aries Susanty; Haryo Santosa; Fani Tania (Department of Industrial Engineering Universitas Muhammadiyah Surakarta, 2017)
This article assesses the implementation level of Green Supply Chain Management (GSCM) practices in SMEs Pekalongan batik business with GreenSCOR approach and mapped out the results with an approach of importance peformance analysis (IPA). The article also devised a strategy to improve the implementation of GSCM practices. Data collection was done by distributing questionnaires and interviews. This article shows that the level of GSCM implementation in small-scale batik SMEs is in the poor category; Whereas, the level of GSCM implementation in medium-scale batik SMEs is in the average category. The results of the mapping show that, for batik SMEs there are indicators that are in quadrant A. Preparation of strategies to improve GSCM practices in batik SME Pekalongan more focused on improving the performance of indicators of use of environmentally friendly raw materials.